Achieving Widespread Impact: CTA's impact pathways based on 23 evaluation reports - Petrutiu, Stefan; Huet, Eva; Khadar, Ibrahim; Leuvenink, Annemiek (Technical Centre for Agricultural and Rural Cooperation, 2016)
This report presents an analysis of the impacts of CTA’s programmes and activities by 75 impact narratives. It looks into the types of impacts and beneficiaries reached, and the division between short- and long-term impacts. The report also includes a chapter which provides an interpretation of causal and chronological impact and another in which lessons learned are discussed.